Risk Assessment and Mitigation in Workplace Safety at Energy Distribution Company PT XYZ - Agus Riyadi; Vita Ratnasari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
PT XYZ has attempted to protect its employees from work accidents through Occupational Safety and Health (OSH) risk assessments, safety transformation, and the digitalization of safety management. However, the company has not achieved zero accidents due to factors such as the large area, many workers, diverse types of work, an unsafe work culture, and budget constraints. Therefore, risk mitigation is crucial for effective safety management. This study uses a combined method of Analytic Hierarchy Process (AHP)- Failure Mode and Effect Analysis (FMEA)- Bow Tie Analysis (BTA)- Similarity to Ideal Solution (TOPSIS) to select the appropriate risk mitigation strategies. The results showed that disruption handling work carries the highest risk, with 14 risks identified, including 7 high risks, 4 medium risks, and 3 low risks. A total of 79 mitigations have been effective, while 127 mitigations need to be implemented as a priority. The highest priority mitigations to reduce the risk of work accidents include the use of volt detectors, routine vehicle inspections, installation of warning signs, SCADA integration, checking climbing ladders, installing grounding, and using personal protective equipment. With the right mitigation steps, PT XYZ is expected to achieve optimal work safety and zero accidents.